Literatura infanto-juvenil de temática homoafetiva: impasses entre a abordagem dos PCN e a representação ficcional - Costa, Lúcia de Lourdes Monteiro (2011)
The objective of this research was to analyze the discourse of the reading proposal from literary texts directed to children and teenagers, from the National Curriculum Parameters and Transversal Themes, relating them to the narrators‟ discursive practices in literary works for children who approach the homoaffection as followed: O menino que brincava de ser (2000) by Georgina da Costa Martins, O gato que gostava de cenoura (2001) by Rubem Alves e É proibido Miar (2002) by Pedro Bandeira, as from Cultural Studies. It was intended to understand the position taken by these storytellers throughout the discourse where the images are underlain (widely used resources in the narratives directed to children and youngsters with ideological purposes) and the discursive behavior of characters, that is, it is sustained a profile directed to exclusion and rejection of the homoaffectionate or even if such speeches provide a rethinking of the prejudices culturally constructed against them. The idea was to observe whether homoaffection is contemplated by the PCN discussions, noting for non-encounters between what the fictional narrator‟s voice says and the reading model of children‟s literature proposed by the PCN (a guiding text of discursive practices in classroom by assisting in the construction of reading curricular of literary text). For that reason, it was established a dialogue with the Discourse Analysis considering that this particular studying field inquires such a practice which is intrinsic to mankind, its society and its history; the paper‟s research source are the discursive activities circulating in society, including the institutional ones. Hypothetically, it was assumed that the reading goals of literary text of Portuguese language indicated by the PCN do not address the homoaffection issue; moreover, regarding the literary works, it is believed that there is resistance to a positive representation of the homoaffectionates. Such reflections are based in theoretical concepts from Cultural Studies, of Semiotic Studies and Discourse Analysis (AD), being supported by the following authors: Bhabha (1998), Escoteguy (2001), Hall (2005), Dias da Silva (2007), Louro (2008), Tadeu da Silva (2007), Lopes (2002), Peirce (1987), Plaza (2003), Foucault (1986), Fernandes (2008), Milanez (2004), Orlandi (2007), among others.